Electronic symptom monitoring in patients with metastatic lung cancer: a feasibility study. Issue 6 (17th June 2020) - Friis, Rasmus Blechingberg; Hjollund, Niels Henrik; Mejdahl, Caroline Trillingsgaard; Pappot, Helle; Skuladottir, Halla
Abstract : Objectives: To design an electronic questionnaire for symptom monitoring and to evaluate the feasibility, usability and acceptability when applied to patients with metastatic lung cancer. Setting: Single-centre feasibility study. Participants: Patients with stage IV lung cancer in antineoplastic treatment. Interventions: This study describes the first three phases of a complex intervention design: phase 1, development of the intervention; phase 2, feasibility testing and phase 3, evaluation of the intervention. In phase 1, items were selected for the questionnaire and adjusted following patient interviews. In phase 2, patients completed the electronic questionnaire weekly during a 3-week feasibility test. In case of symptom deterioration, a nurse was notified with the aim to contact the patient. In phase 3, patients evaluated phase 2 by paper questionnaires, and interviews were conducted with the participating nurses. Primary outcome measures: The study outcomes: phase 1, usability and relevance; phase 2, recruitment rate, compliance and threshold functionality and phase 3, usability, acceptability and relevance. Results: In phase 1, a questionnaire was designed and reviewed by patients (n=8). The interviews revealed high usability and relevance of the intervention. For phases 2 and 3, 20 of 29 approached patients (69%) responded to the questionnaire on a weekly basis. Two patients did not complete any questionnaires (compliance 90%). The remaining 18 patients completed 65 of a total of 72 possible questionnaires (7 missed, 93% completed). Reported symptoms led to a phone call from a nurse in 30% of the responses. The patients reported high usability and acceptability of questionnaire and software. The substance of the telephonic conversations was relevant, and the study set-up was logistically acceptable. Conclusions: An electronic questionnaire designed for symptom monitoring revealed high usability, acceptability and relevance in the target population. In conclusion, the study set-up was considered feasible for a randomised controlled trial. Trial registration number: NCT03529851 .